Sexually transmitted and reproductive tract infections in symptomatic clients of pharmacies in Lima, Peru. Issue 2 (17th August 2006) - García, P J; Cárcamo, C P; Chiappe, M; Holmes, K K
Abstract : Objective: To determine prevalences and predictors of sexually transmitted and reproductive tract infections among men and women seeking care at pharmacies. Methods: Men and women with urethral discharge or dysuria and vaginal discharge were enrolled at 12 central and 52 smaller pharmacies in Lima, Peru. All participants answered a questionnaire. Men provided urine for polymerase chain reaction (PCR) testing for Neisseria gonorrhoeae and Chlamydia trachomatis, and for leucocyte esterase testing. Women provided self-obtained vaginal swabs for PCR testing for N gonorrhoeae and C trachomatis, Trichomonas vaginalis culture and bacterial vaginosis and Candida . Results: Among 106 symptomatic men, N gonorrhoeae and C trachomatis were detected in 34% and were associated with urethral discharge compared with dysuria only (odds ratio (OR) 4.3, p = 0.003), positive urine leucocyte esterase testing (OR 7.4, p = 0.009), less education (OR 5.5, p = 0.03), and with symptoms for <5 days (OR 2.5, p = 0.03). Among 121 symptomatic women, 39% had bacterial vaginosis or T vaginalis, and 7.7% had candidiasis. N gonorrhoeae and C trachomatis were detected in 12.4% of the women. Overall, 48.8% had one or more of these infections. No factors were associated with vaginal infection, and only symptoms of vaginal discharge for <5 days were associated with N gonorrhoeae and C trachomatis (OR 4.0, p = 0.02). The main reason reported for seeking advice at pharmacies by both men and women was trust in pharmacy workers. Conclusions: Among men and women presenting to pharmacies with urethral and vaginal symptoms, rates of urethral and vaginal infections were comparable to those found in other clinical settings. Pharmacies can contribute to the care and prevention of sexually transmitted infection in developing countries.